Mitigasi Serangan Distributed Denial of Service (DDoS) pada Arsitektur Software Defined Networking (SDN) Menggunakan Firewall Iptables - Heru Saputra (Institute of Information Technology and Social Science (IITSS), 2021)
Distributed Denial of Service (DDoS) attacks are one of the main threats to the availability of network services in the era of information technology globalization. Software Defined Networking (SDN) architecture offers the convenience of centralized network management, but on the other hand, it also has potential vulnerabilities to cyber attacks, especially DDoS. This study aims to mitigate DDoS attacks on SDN architecture in wireless networks using iptables firewall. The research method used is action research which includes the stages of diagnosis, action planning, action implementation, evaluation, and learning. The simulated attack is Ping of Death using mininet on a virtual machine. The test results show that before mitigation the number of attack packets reached 1,021 M packets per second, while after mitigation using iptables the number of packets decreased significantly to 8.34 K packets per second. Thus, the implementation of iptables firewall is proven effective in suppressing DDoS attack traffic on SDN architecture in wireless networks.